Faktor-faktor yang Mempengaruhi Keputusan Petani Mangga dalam Pemilihan Pasar di Kabupaten Indramayu - Andriani, Rani; Rasmikayati, Elly; Mukti, Gema Wibawa; Fatimah, Sri (Jurnal Penyuluhan, 2019)
Increasing domestic demand for mangoes in recent years has increased rapidly, not only in terms of quantity but also in terms of quality of mango, especially for modern markets. But only a small part of the mango which could entered the modern market. Understanding of farmers' access to markets is needed to increase farmers' capacity as an effort to improve farmers' welfare. The purpose of this research were to: 1) Analyze socioeconomic characteristics of mango farmers in Indramayu Regency; 2) Analyze the mango marketing channelin Indramayu District; 3) Analyze the factors that influence the decision of mango farmers in market selection in Indramayu District. This research is a quantitative research with 130 mango farmers who were taken by using multi stage random sampling. Data were analyzed descriptively as well as logistic regression analysis. The results showed that most of the farmers were in productive age, had completed primary school education, had